(3JaSjQ GdChRGf hGdCcjGd GdeSJYedI aj GdWHs - (3eLghds
(3ChdgG (B:s
(3GdOQge ef KeGfjI YTQ bjQGWkG , hef NeSI YTQ bjQGWkG s
(3BNQgG (B:s
(3hgPg GdCcjGd hGdChRGf cKjQI LOkG , hJcGO Cf Jchf ZjQ eJfGgjI hGdMeO ddg s
(3Vef eLehY s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B61 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs